1998
DOI: 10.1212/wnl.51.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in children and sickle-cell disease

Abstract: Sickle-cell disease plays a disproportionately high role in childhood stroke when a biracial population is surveyed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
1
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(166 citation statements)
references
References 27 publications
(9 reference statements)
6
152
1
7
Order By: Relevance
“…The Baltimore-Washington Cooperative Young Stroke Study found an incidence of HS of 285 per 100,000 person-years in children with SCD, nearly a 250-fold risk over unaffected children [32]. The Cooperative Study of Sickle Cell Disease found a more modest increase in HS incidence in children and young adults, ranging from 17 to 44 per 100,000 person-years [33].…”
Section: Special Populationsmentioning
confidence: 99%
“…The Baltimore-Washington Cooperative Young Stroke Study found an incidence of HS of 285 per 100,000 person-years in children with SCD, nearly a 250-fold risk over unaffected children [32]. The Cooperative Study of Sickle Cell Disease found a more modest increase in HS incidence in children and young adults, ranging from 17 to 44 per 100,000 person-years [33].…”
Section: Special Populationsmentioning
confidence: 99%
“…The risk of stroke is 250 times greater in adolescents with SCD than in nonsickle individuals (Earley et al, 1998), and it is estimated that in addition to children who experience overt stroke, a further 20-30% will suffer silent infarctions, but with no apparent phenotypic consequence (Earley et al, 1998;Kinney et al, 1999;Moser et al, 1996). SCD is the major cause of stroke in childhood (Hoppe et al, 2003), with significant recurrence rates, which can lead to severe complications such as permanent neurological damage, residual motor deficits, cognitive impairment, and death (Flanagan et al, 2013;Sebastiani et al, 2005).…”
Section: Stroke In Scdmentioning
confidence: 99%
“…Cerebral infarction is the common cause of stroke in the first two decades of life and from the fourth decade onward; whereas, hemorrhagic stroke occurs commonly in the third decade (Ohene-Frempong et al, 1998). Clinical stroke with focal signs lasting more than 24 h is more common in children (Earley et al, 1998). Regardless of brain structural abnormalities, children with sickle disease with or without a history of overt stroke tend to have lower cognitive ability (Hogan et al, 2006;Noll et al, 2001;Watkins et al, 1998), andocular (Elagouz et al, 2010;Nagpal et al, 1977) and ophthalmic (Babalola and Wambebe, 2005;To and Nadel, 1991) complications.…”
Section: Neurological Complicationsmentioning
confidence: 99%